Philosophical perspectives on esotericism: from the 19th century to the present - Pitkänen, Olli (Routledge studies in the philosophy of religion, 2025)
"This volume offers the first systematic philosophical study of esotericism and late modern philosophy. It addresses fundamental philosophical questions related to esotericism and reveals that esoteric ideas have had decisive impact on countless important philosophers, even if this fact has been neglected in contemporary philosophy. The first section of the book is dedicated to substantial and methodological questions. What is philosophy, what is esotericism, and how should we think about their relationship? The second section is more historically oriented, and it is divided in three parts. Part 1 is concerned with German romanticism and idealism, with a specific focus on the influence of esotericism on Hegel and Schelling, as well as the connection between romanticism and Kabbalah in the work of Gershom Scholem. Part 2 explores esotericism in phenomenology, pragmatism, and post-idealism, specifically in the work of William James, Martin Heidegger, Henri Bergson, and Roy Bhaskar. Finally, Part 3 takes up esotericism in Islamic and Jewish philosophy. Philosophical Perspectives on Esotericism will appeal to scholars and advanced students working in philosophy of religion, history of philosophy, and religious studies"--